Gene p53 Mutations after the Induction of 7,12-Dimethylbenz(a)anthracene (DMBA) and Administration of Anti-Carcinogenesis Properties of Gynura procumbens in Sprague Dawley Rats - abdul Gofur (Biomedical Engineering, 2015)
Objective: The aim of this research is to study p53 gene mutations in the mammary gland ofDMBA-induced Sprague Dawley rats treated with the ethanol extract of Gynura procumbens.Methods: Sprague Dawley female rats aged 40 days were used. DMBA positive control animalswere treated with 20 mg/kg bw DMBA; Gynura-extract positive control animals were treatedwith 300 or 750 mg/kgbw G. procumbens extract without DMBA treatment; experimentalanimals were treated with 300 or 750 mg/kg bw G. procumbens extract and 20 mg/kg bwDMBA, intragastric, while negative control animals neither treated with DMBA nor G.procumbens extract. Each group consists of 5 animals. Palpation and necropsy of mammaryglands was conducted at the end of the experiment. Mutation of p53 was studied in exon-6 of thisgene, in triple or less, depended on available samples.Result: G. procumbens extract generally suppress tumor incidence in DMBA treated animals.p53 sequence showing some point mutations which also affect on its amino acid sequence, but itwas not exclusively occurred in DMBA treated animals.Conclusion: Based on this research we can not conclude that tumor incidence in this experimentwas resulted by the mutation of p53 gene.